Plataforma web para la gestión de información en iniciativas sobre energías renovables - García-Salas, Andrés de Jesús (Instituto Tecnológico de Costa Rica, 2019)
Over the last few years, information technologies have promoted improvements in an unrivaled number of elds, increasing the precision of tasks, simplifying processes and even transforming work practices. In the case of institutions that have energy production systems based on renewable energy, there is a need to manage the millions of data generated every second by these systems, creating some usefulness for them in the business intelligence required by this process. All this with the purpose of facilitating the administrative process on this system. Due to the above, a sixteen-week work was carried out, where multiple processes of software development according to the engineering standard were implemented, oriented towards the construction of a solution for this productive sector. These processes include the proposal of the solution, the de nition of the requirements, design, and development of the software platform. With this, it was possible to obtain a solution adapted in conjunction with a previously developed solution, which together makes it easier to manipulate this massive data. Keywords| Data Science, Big Data, Prediction model, Photovoltaic panels, R, REST- Ful API
Práctica profesional (Bachillerato en Ingeniería en Computación) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Computación, 2019.
Keywords: Paneles solares; Producción energética; Tecnologías de la Información; Software; Medio Ambiente; Solar panels; Energy production; Information technology; Software; Environment; Research Subject Categories::TECHNOLOGY::Information technology